STROKE ISKEMIK AKUT PASCA PPCI (PRIMARY PERCUTANEOUS CORONARY INTERVENTION) : SEBUAH LAPORAN KASUS MENGENAI STEMI ANTEROEKSTENSIF: ACUTE ISCHAEMIC STROKE POST PPCI (PRIMARY PERCUTANEOUS CORONARY INTERVENTION) : A CASE REPORT ON ANTEROSEPTAL STEMI - Nisa El Hasanah; Hafiz Ahmad Ikhsanul Yannas; Putri Theresia L.A Bancin; Fikra Clara Anjelita; Gita Annisa Raditra (Jurnal Kedokteran STM (Sains dan Teknologi Medik), 2026)
Acute ischemic stroke is a serious but rare complication following primary percutaneous coronary intervention (PPCI) in patients with ST Elevation Myocardial Infarction (STEMI). The risk increases in the presence of heavy coronary thrombus and left ventricular dysfunction. A 54-year-old man presented with left chest pain radiating to the neck, accompanied by palpitations and diaphoresis. Electrocardiography showed ST segment elevation in leads V1–V6 consistent with extensive anterior STEMI. Coronary angiography revealed subtotal occlusion and thrombus in the proximal left anterior descending artery (LAD), severe stenosis of the left circumflex artery (LCX), and chronic total occlusion (CTO) of the right coronary artery (RCA). The patient received antiplatelet therapy, statins, insulin, and underwent PPCI on the LAD. Four hours post-PPCI, the patient experienced decreased consciousness and left-sided hemiparesis. Head CT scan showed a large right temporoparietal infarct. Echocardiography showed an ejection fraction of 36% with spontaneous echo contrast (SEC) supporting cardioembolic embolism. After two weeks of intensive care, hemodynamic condition improved with residual left hemiparesis and global aphasia. In conclusion, acute ischemic stroke post-PPCI in STEMI is associated with high thrombus burden, left ventricular dysfunction, and risk of systemic embolism, thus requiring close neurological monitoring post reperfusion. AbstrakStroke iskemik akut merupakan komplikasi serius namun jarang terjadi setelah primary percutaneous coronary intervention (PPCI) pada pasien ST Elevation Myocardial Infarction (STEMI). Risiko meningkat pada kondisi trombus koroner berat dan disfungsi ventrikel kiri. Dijumpai Seorang laki-laki 54 tahun datang dengan nyeri dada kiri menjalar ke leher disertai palpitasi dan diaforesis. Elektrokardiografi menunjukkan elevasi segmen ST pada sadapan V1–V6 yang sesuai dengan STEMI anteroekstensif. Angiografi koroner menunjukkan subtotal oklusi dan trombus pada left anterior descending artery (LAD) proksimal, stenosis berat left circumflex artery (LCX), serta chronic total occlusion (CTO) right coronary artery (RCA). Pasien mendapat terapi antiplatelet, statin, insulin, dan dilakukan PPCI pada LAD. Empat jam pasca-PPCI, pasien mengalami penurunan kesadaran dan hemiparesis sinistra. CT-scan kepala menunjukkan infark luas temporoparietalis kanan. Ekokardiografi menunjukkan ejeksi fraksi 36% dengan spontaneous echo contrast (SEC) yang mendukung emboli kardioembolik. Setelah dua minggu perawatan intensif, kondisi hemodinamik membaik dengan sisa hemiparesis sinistra dan afasia global. Kesimpulannya Stroke iskemik akut pasca-PPCI pada STEMI berkaitan dengan tingginya beban trombus, disfungsi ventrikel kiri, dan risiko emboli sistemik sehingga diperlukan pemantauan neurologis ketat pasca reperfusi.